Lipoid Proteinosis - A Rarity in An Adult - Karthikeya Patil; Sanjay CJ; Mahima V Guledgud; Prasannasrinivas Deshpande; Aishwarya R; Nagabhushana Doggalli (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Lipoid proteinosis is a rare genodermatosis with autosomal recessive inheritance. It isa multisystem disorder characterized by progressive deposition of hyaline material in the skin, mucousmembrane and different organs of the body. The disease is presented by dermatological, laryngeal,ophthalmological, and neurological manifestations. Involvement of oral mucosa may lead to xerostomia anddysphagia; involvement of larynx and eyes results in hoarseness of voice at early infancy and moniliformblepharosis. Extracutaneous involvement includes neurological manifestations like psychosis, partialcomplex seizures, anger, panic attacks, and progressive amnesia. Till date around 300 cases have beenreported in literature.Case Report: A 63 years old male patient reported with chief complaints of pain in the right and left cheekregion, difficulty in swallowing food and dryness of mouth.Conclusion: Lipoid Proteinosis requires multidisciplinary opinion and evaluation by dermatologists,ophthalmologists, otolaryngologists, neurologists and psychiatrist. Clinical features and histopathologicalevaluation aids in the confirmation of the disease. Lipoid proteinosis should be considered one among thedifferential diagnosis when patient reports with difficulty in mouth opening, enlarged tongue, difficult inchewing and swallowing.